Training on Reference Manager Tool (Mendeley) for Students of Faculty of Islamic Studies, Universitas Muhammadiyah Bengkulu - Susanti, Meri; Kusmiarti, Reni; Mamnun, Hairo; AR, Rosmita; Natalia, Nela (CV Media Inti Teknologi, 2024)
Reference Manager Tool (Mendeley) training for students at the Faculty of Islamic Religion, Muhammadiyah University was carried out with the aim of assisting students in creating bibliographies automatically and searching for references from leading international and national journals that have accreditation, especially in writing quotations. Training is carried out through lecture methods, practice and question and answer sessions led by the team. This activity was held at campus IV, Muhammadiyah University on Wednesday, December 6 2023, with the participation of 95 students from the Faculty of Islamic Religion, Muhammadiyah University, Bengkulu. The implementation of this service uses several techniques, namely lectures, discussions and demonstrations. The implementation stages of this service consist of several opening and introduction sessions, introduction to Mendeley installation and initial preparation, Mendeley account creation, main feature training, reference organization, use of citation tools, making a bibliography, question and answer sessions and practice. This service concludes that 80% of students understand well how to insert citations and create a bibliography using Mendeley. This service provides significant benefits and makes a positive contribution in preparing students at the Faculty of Islamic Religion, Muhammadiyah University of Bengkulu to face academic challenges, as well as assisting in producing more structured written work. Some suggestions that should be considered for better implementation of service include conducting initial surveys to identify student knowledge and needs, providing complete and easily accessible training materials in various formats, conducting evaluations and collecting feedback from training participants to improve and adjust the program in the future.